Impact of Moringa oleifera leaf extract on renal histopathology, malondialdehyde, superoxide dismutase, and calcium oxalate crystals in rats (Rattus norvegicus) exposed to ethylene glycol - Dewa Ketut Meles; Imam Mustofa; Wurlina Wurlina; Zulfi Nur Amrina Rosyada; Aswin Rafif Khairullah; Kadek Rachmawati; Astri Nur Hidayah; Niluh Suwasanti; Rheza Imawan Mustofa; Adeyinka Oye Akintunde; Riza Zainuddin Ahmad; Fitrine Ekawasti; et al. (Open Veterinary Journal)
Background: Nephrolithiasis is a kidney disorder caused by the formation of crystals through physiological and chemical processes in the body, with calcium oxalate being a major contributor. Moringa oleifera leaves are known for their antioxidant, diuretic, and anti-inflammatory properties, containing alkaloids, flavonoids, polyphenols, polysaccharides, saponins, phenolics, and tannins.